Understanding Gen Z: The Role of Emotional Engagement, Promotion, and Social Influence on Purchase Intention Toward a Local Beauty Brand, Mediated By Product Scarcity - Ni Ketut Yuliani Pramesti; Putu Dyah Permatha Korry (Cakrawala Repositori IMWI)
This research examined how emotional engagement, promotion, and social influence shaped Generation Z’s purchase intention toward a local Indonesian beauty brand, Somethinc, with product scarcity tested as a mediating variable. Grounded in the Theory of Planned Behavior, this study addressed inconsistencies in previous consumer behavior research by proposing perceived scarcity as a psychological mechanism that links marketing stimuli to purchase intention. A quantitative causal-associative research design was applied to 230 Generation Z consumers in Denpasar City, selected through purposive sampling based on the Slovin formula from a population of 227,000 individuals. Data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The measurement model confirmed convergent validity, discriminant validity, and construct reliability. The structural model results showed that emotional engagement, promotion, and social influence each had positive and significant direct effects on purchase intention and product scarcity. Furthermore, product scarcity positively influenced purchase intention and significantly mediated the relationships between emotional engagement, promotion, social influence, and purchase intention. The model explained 75.7% of the variance in purchase intention. These findings extend the Theory of Planned Behavior by positioning perceived scarcity as a mediating mechanism and provide practical implications for local beauty brands in integrating emotional branding, promotional strategies, and social proof approaches with appropriate scarcity marketing strategies. Future research should examine the model across different cities, product categories, and additional variables, such as brand trust and fear of missing out.